2016
DOI: 10.1152/jn.00018.2016
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of visual category representation in the macaque inferior temporal cortex

Abstract: Object categories are recognized at multiple levels of hierarchical abstractions. Psychophysical studies have shown a more rapid perceptual access to the mid-level category information (e.g., human faces) than the higher (superordinate; e.g., animal) or the lower (subordinate; e.g., face identity) level. Mid-level category members share many features, whereas few features are shared among members of different mid-level categories. To understand better the neural basis of expedited access to mid-level category … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 57 publications
6
40
0
Order By: Relevance
“…Our findings on the emergence of categorization as a function of time showed that cells discriminated faces from nonfaces before they performed a finer categorization within the face stimulus space. This is consistent with findings showing a decoding of different stimulus categories as a function of time from stimulus onset in the macaque inferotemporal cortex (61). Specifically, the authors found an earlier representation of midlevel categories (e.g., face vs. body and human vs. monkey) compared with subordinate-level categories (such as person identity).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings on the emergence of categorization as a function of time showed that cells discriminated faces from nonfaces before they performed a finer categorization within the face stimulus space. This is consistent with findings showing a decoding of different stimulus categories as a function of time from stimulus onset in the macaque inferotemporal cortex (61). Specifically, the authors found an earlier representation of midlevel categories (e.g., face vs. body and human vs. monkey) compared with subordinate-level categories (such as person identity).…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, the authors found an earlier representation of midlevel categories (e.g., face vs. body and human vs. monkey) compared with subordinate-level categories (such as person identity). The latencies of the OFC face cells are generally above the ones reported in the temporal cortex, ranging from 80 to 120 ms using similar methods for computing the latency, i.e., a threshold on the instantaneous spike density function (61)(62)(63)(64). How the OFC face cells may combine or multiplex input from the temporal regions remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…animal-plane and animal-car) category information was also noticeable in the temporal dynamics of category information ( Supplementary Fig. S2A; Dehaqani et al, 2016).…”
Section: Temporal Dynamics Of Category and Variation Processingmentioning
confidence: 91%
“…car-plane) and superordinate-level (e.g. animal-plane and animal-car) category information was also noticeable in the temporal dynamics of category information 53 (Supplementary Fig. S2A ).…”
Section: Resultsmentioning
confidence: 96%